2017
DOI: 10.3389/fphar.2017.00237
|View full text |Cite
|
Sign up to set email alerts
|

Rolipram Improves Outcome in a Rat Model of Infant Sepsis-Induced Cardiorenal Syndrome

Abstract: While the mortality rate associated with sepsis in children has fallen over the years, it still remains unacceptably high. The development of both acute cardiac dysfunction and acute kidney injury during severe sepsis is categorized as type 5 cardiorenal syndrome (CRS) and is poorly understood in infants. To address this lack of understanding and the need for an appropriate animal model in which to conduct relevant preclinical studies, we developed a model of infant sepsis-induced CRS in rat pups then evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 69 publications
0
13
0
3
Order By: Relevance
“…Treatment with rolipram improves renal blood flow, protects renal microcirculation and improves glomerular filtrate rate and renal function in a murine model of CLP-induced sepsis, even when administered 6 h after CLP (93). Rolipram treatment also improved renal and cardiac function leading to improved survival in septic rat pups (94). PDE4 inhibitors, rolipram and roflumilast, have been shown to reduce leukocyte-endothelial interactions which inhibits inflammatory cell influx, and reduce capillary leakage during LPS-induced inflammation (95,96).…”
Section: Phosphodiesterase (Pde) Inhibitorsmentioning
confidence: 99%
“…Treatment with rolipram improves renal blood flow, protects renal microcirculation and improves glomerular filtrate rate and renal function in a murine model of CLP-induced sepsis, even when administered 6 h after CLP (93). Rolipram treatment also improved renal and cardiac function leading to improved survival in septic rat pups (94). PDE4 inhibitors, rolipram and roflumilast, have been shown to reduce leukocyte-endothelial interactions which inhibits inflammatory cell influx, and reduce capillary leakage during LPS-induced inflammation (95,96).…”
Section: Phosphodiesterase (Pde) Inhibitorsmentioning
confidence: 99%
“…5 a and b). This effect was not observed in the group treated with the free drugs, although PDE4 inhibition has been proven to attenuate acute renal failure in sepsis and endotoxemia [ 24 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…One representative PDE4 inhibitor is rolipram, which is a novel PDE4 inhibitor. Rolipram improves cardiac and renal function through the inhibition of cytokine overexpression in a rodent model of sepsis [ 24 , 25 ]. Neutrophils are the most important cell in the host response to bacterial infection [ 26 ], and their migration is a fundamental component of the immune response elicited by bacteremia [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PDE4 family is encoded by four genes, PDE4A , PDE4B , PDE4C and PDE4D [ 178 ] and was shown to be involved in the excitation-contraction coupling regulation, especially in rodents. It has been recently suggested that PDE4 inhibitors could be beneficial in treating sepsis in infants with cardio-renal syndrome (CRS) since they are effective in improving cardiac function in a rat model suffering from sepsis-induced acute cardiac dysfunction and kidney injury [ 179 ]. In addition, PDE4 depletion stabilized the endothelial barrier by reducing the atrial natriuretic peptide (ANP)-induced vascular permeability and, therefore, was efficient in maintaining the plasma volume [ 180 ].…”
Section: Cyclic Nucleotide Phosphodiesterases (Pdes)mentioning
confidence: 99%